In Vitro Biodegradability of Phosphorylated Hyaluronic Acid by Testicular Hyaluronidase - Elvira A. Khaybrakhmanova; Stanislav V. Kozyrev; Irina Yu. Ponedel’kina (Chemistry Proceedings)
One of the most important characteristics for the development of biomaterials based on hyaluronic acid (HA) and its chemically modified derivatives is resistance to hyaluronidases (HA-ase), which are responsible for the degradation of HA macromolecules. In this work, samples of phosphorylated (HA-P) low- and high-molecular-weight HA (43 kDa and 0.5–0.7 MDa) were obtained by conventional stirring of HA/P2O5 mixtures at different molar ratios (1:0.2, 1:0.5, 1:1, and 1:2) and exposed to bovine testicular HA-ase (60 or 600 ME/mL, [HA] = 4 mg/mL of citrate buffer, pH 6.3, 16–18 h). It was found that the biodegradability of the HA-P samples obtained at the ratio of 1:0.2, 1: 0.5, and 1:1 was at the level of native HA or higher. Only samples obtained at a HA/P2O5 ratio of 1:2 showed resistance to HA-ase; their biodegradability was 13–54% lower compared to that of native HA.